Investigating energetic electron precipitation through combining ground‐based and balloon observations. Issue 1 (21st January 2017) - Clilverd, Mark A.; Rodger, Craig J.; McCarthy, Michael; Millan, Robyn; Blum, Lauren W.; Cobbett, Neil; Brundell, James B.; Danskin, Donald; Halford, Alexa J.
Abstract: A detailed comparison is undertaken of the energetic electron spectra and fluxes of two precipitation events that were observed in 18/19 January 2013. A novel but powerful technique of combining simultaneous ground‐based subionospheric radio wave data and riometer absorption measurements with X‐ray fluxes from a Balloon Array for Relativistic Radiation‐belt Electron Losses (BARREL) balloon is used for the first time as an example of the analysis procedure. The two precipitation events are observed by all three instruments, and the relative timing is used to provide information/insight into the spatial extent and evolution of the precipitation regions. The two regions were found to be moving westward with drift periods of 5–11 h and with longitudinal dimensions of ~20° and ~70° (1.5–3.5 h of magnetic local time). The electron precipitation spectra during the events can be best represented by a peaked energy spectrum, with the peak in flux occurring at ~1–1.2 MeV. This suggests that the radiation belt loss mechanism occurring is an energy‐selective process, rather than one that precipitates the ambient trapped population. The motion, size, and energy spectra of the patches are consistent with electromagnetic ion cyclotron‐induced electron precipitation driven by injected 10–100 keV protons. Radio wave modeling calculations applying the balloon‐based fluxes were used for the first time and successfully reproduced the ground‐based subionospheric radio wave and riometer observations, thus finding strong agreement between the observations and the BARREL measurements. Key Points: Modeling of ground‐based radio wave observations with BARREL‐specified electron precipitation fluxes at energies of ~1.0–1.2 MeV Two precipitation patches, with longitudinal dimensions of 1.5–3.5 h in MLT, are observed to drift westward passed the BARREL balloon A peaked spectrum is suggested, but improved instrumentation is required to unambiguously resolve form of the electron precipitation